Crustal architecture, geodynamics and structural evolu-tion of en nuhud basin area, kordofan region, Sudan - Elmansour, Asim Abubabakr; Alimam, Omar (International Journal of Advanced Geosciences, 2017)
Borehole data, geophysical investigations and remote-sensing prospection were used to demonstrate structural setting of the study area. Up to lifting, erosion subsidence and sedimentation activities intervene in the completion of the present geological setting. Different fault systems of NNW-SSE and E-W trends that coincide with the regional structural trends control the formation of En Nuhud Basin. Strike-slipping along the NNW-SSE system manifests at the southeastern part of the basin. An age of Precamberian for the formation of these structures is proposed. Later in the Cainozoic, the area was subjected to tensional forces, and hence a pull-apart basin is formed as a half graben with stepping depth in the south. The thickness of the sedimentary sequence generally ranges between few meters at the boundaries and about 1000 meters at the southern part of the basin. The study area seems to be tectonically active during the subsequent time. Sync-tectonic deposition is clearly shown in the relatively thick Superficial Deposits above the subsided zones. Elevation of the study area above the surroundings indicates an inversion stage for the basin, and presence of far-field effects is suitable in this case.